Survey of Aedes Sp. Larvae Density in Water Storage Containers in Pinang Merah Subdistrict, Jambi City - Sukmal Fahri; Emilia Chandra; Lilis Prihastini (Gema Lingkungan Kesehatan, 2025)
Jambi City, as the capital of Jambi Province, has seen rapid development of new residential areas. However, not all areas are served by the municipal water supply (PDAM), leading to the storage of water outside homes. The presence of vacant land has further contributed to the proliferation of mosquitoes, and the expansion of residential areas is suspected to increase cases of dengue fever (DHF). This situation is favorable for Aedes aegypti mosquitoes, which thrive near clean water sources. This study is a descriptive survey using a cross-sectional method to describe the density level of Aedes sp. larvae. The research was conducted from October to December 2023 in Pinang Merah Subdistrict, Jambi City, and larval identification was carried out in the Environmental Health Department Laboratory of the Jambi Health Polytechnic (Poltekkes Kemenkes Jambi). Water storage containers found to contain larvae included metal drums, plastic drums, and cement-coated ponds, with a prevalence of 33.3%. The presence of larvae outside homes is closely related to breeding sites that collect rainwater, which then become larval habitats. From the analysis, a House Index (HI) of 25% and a Larvae-Free Index of 75% were obtained. The study concludes that the density of Aedes sp. larvae in water storage containers in Pinang Merah Subdistrict is at a moderate level.